Segmental neurofibromatosis with deep schwannoma - Wallace A Smith (Indian Dermatology Online Journal, 2016)
An elderly patient presented with two clusters of asymptomatic fleshy and pedunculated papules. Biopsy of the papules was consistent with neurofibromas. Decades prior she had undergone a surgery for the excision of a large schwannoma. Given her lack of other neurofibromatosis findings, the patient was diagnosed with multisegmental neurofibromatosis (multi-SN) with deep schwannoma, a possible new phenotype of SN. Because this entity may be associated with internal malignancy, it is important to screen and educate these patients as well as to provide regular follow-up.